PHARMACEUTICAL NANOTECHNOLOGY: FORMULATION AND IN VIVO EVALUATION OF CURCUMIN-LOADED NANOSUSPENSIONS FOR ENHANCED ANTI-INFLAMMATORY EFFICACY - Elisa Issusilaningtyas; Sarah Williams; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2025)
Curcumin, a natural polyphenol derived from Curcuma longa, is well-regarded for its potent anti-inflammatory properties. However, its therapeutic application is severely hampered by its extremely low aqueous solubility and poor oral bioavailability, which leads to suboptimal absorption and limited clinical efficacy. Pharmaceutical nanotechnology offers a promising strategy to overcome these biopharmaceutical challenges. This research aimed to formulate a stable curcumin nanosuspension to significantly enhance its dissolution rate and bioavailability, and to subsequently evaluate its improved anti-inflammatory efficacy in an in vivo model. A curcumin nanosuspension was prepared using the high-pressure homogenization technique, stabilized with Poloxamer 188. The formulation was characterized for particle size, polydispersity index (PDI), and zeta potential. An in vivo anti-inflammatory study was conducted using the carrageenan-induced paw edema model in Wistar rats, comparing the efficacy of the nanosuspension against a conventional coarse curcumin suspension. The optimized nanosuspension exhibited a narrow particle size distribution with a mean diameter of 210 nm and a zeta potential of -28.5 mV, indicating good physical stability. The in vivo evaluation demonstrated that the curcumin nanosuspension produced a significantly greater inhibition of paw edema (72.4%) compared to the coarse curcumin suspension (28.1%) at the same dose (p < 0.01). Formulating curcumin into a nanosuspension is a highly effective strategy for overcoming its inherent bioavailability limitations. This nanotechnological approach dramatically enhances curcumin’s anti-inflammatory activity, validating its potential as a powerful therapeutic agent for inflammatory conditions.